Past and Future Work on Radiobiology Mega Studies: A Case Study at Argonne National Laboratory - Haley, Benjamin (2011)
Between 1952 and 1992 more than 200 large radiobiology studies were conducted in research institutes throughout Europe, North America and Japan to determine the effects of external irradiation and internal emitters on the life span and tissue toxicity development in animals. At Argonne National Laboratory, 22 external beam studies were conducted on nearly 700 beagle dogs and 50,000 mice between 1969 and 1992. These studies helped to characterize the effects of neutron and gamma irradiation on lifespan, tumorigenesis, and mutagenesis across a range of doses and dosing patterns. The records and tissues collected at Argonne during that time period have been carefully preserved and redisseminated. Using these archived data ongoing statistical work has been done and continues to characterize quality of radiation, dose, dose rate, tissue, and gender specific differences in the radiation responses of exposed animals. The ongoing application of newly developed molecular biology techniques to the archived tissues has revealed gene specific mutation rates following exposure to ionizing irradiation. The original and ongoing work with this tissue archive is presented here as a case study of a more general trend in the radiobiology mega studies. These experiments helped form the modern understanding of radiation responses in animals, and continue to inform development of new radiation models. Recent archival efforts have facilitated open access to the data and materials produced by these studies and so a unique opportunity exists to expand this continued research.